2019
DOI: 10.33476/jtiy.v6i1.599
|View full text |Cite
|
Sign up to set email alerts
|

HelloCare: APLIKASI MANAJEMEN PENGETAHUAN BERBASIS ANDROID UNTUK TENAGA KESEHATAN

Abstract: Technology Development in the health sector is one of the main targets in mobile application development today. Sharing knowledge and experience among health workers are challenging to implement because of the lack of a place to exchange their ideas. Based on this background, we built a HelloCare application on the Android platform as an application of knowledge management for health workers. Testing of the application using the System Usability Scale (SUS) to 30 respondents consisting of nurses and physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In that regard, the development of technology is expected to be able to facilitate health services for all needs as well as the spread of health information and knowledge quickly (Hayurani et al, 2019). And in concern with that, android-based applications can provide information more quickly and can be used and accessed anytime and anywhere (Sayekti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In that regard, the development of technology is expected to be able to facilitate health services for all needs as well as the spread of health information and knowledge quickly (Hayurani et al, 2019). And in concern with that, android-based applications can provide information more quickly and can be used and accessed anytime and anywhere (Sayekti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Usability Testing menggunakan metode System Usability Scale (SUS) telah dilakukan pada beberapa bidang seperti bidang pendidikan yaitu oleh (Supriyadi et al, 2020), (Nuriman & Mayesti, 2020), (Pal & Vanijja, 2020) dan (Dimas Setiawan et al, 2020), bidang pemerintahan seperti (Kaban et al, 2020), (Sasmito et al, 2019), (Ependi, Putra, et al, 2019), hingga beberapa aplikasi yang diperuntukkan untuk kepentingan publik seperti e-commerce dan aplikasi berita (Ramadhan, 2019) (Sembodo et al, 2021). Selain itu, evaluasi pada penerapan Knowledge Management System (KMS) telah banyak dilakukan pada beberapa perusahaan dengan berbagai tujuan seperti pada (Hidayad & Fauziati, 2018) dan (Hayurani et al, 2019).…”
Section: Tinjauan Literaturunclassified
“…Peneliti menggunakan metode System Usability Scale (SUS) untuk mengetahui tingkat penerimaan model baru tersebut, didapatkan hasil bahwa sistem diterima akan tetapi belum mencapai skor ideal. Sementara berdasarkan penelitian oleh (Hayurani et al, 2019) yang membangun Knowledge Management Sysem (KMS) dengan tujuan untuk menjadi sarana bagi tenaga Kesehatan untuk terus berbagi pengetahuan yang dimiliki, pengujian dilakukan kepada 30 responden dan didapatkan hasil bahwa sistem memiliki usability yang baik dengan efektifitas yaitu 80.88%.…”
Section: Tinjauan Literaturunclassified
“…Researchers used the System Usability Scale (SUS) method to determine the level of acceptance of the new model, the results showed that the system was accepted but had not yet reached the ideal score. Meanwhile, based on research by [14] who built a Knowledge Management System (KMS) with the aim to be place where the health workers can store, share or receive new knowledge, testing was carried out on 30 respondents and the results showed that the system had good usability with effectiveness is 80.88%.…”
Section: Introductionmentioning
confidence: 99%